Evaluation of the in-vivo antitrypanosomal activity of the crude extract of Moringa oleifera (lam) against rats infected with Trypanosoma brucei - Datti , Yau; Musa , Ibrahim; Ali , Usman Lado; Mustapha, Abdulhadi; Tijjani , Yahya Ahmad; Koki , Isa Baba; Ado , Abubakar Sulaiman; Musa , Shuaibu Muhammad; Adamu, Garba Alhaji; Umar, Aliyu (GSC Biological and Pharmaceutical Sciences, 2020)
The anti-typanosomal effect of the crude extract of the leaves of Moringa oleifera was determined in-vivo in Trypanosoma brucei-infected rats. In the study, twenty five rats (weighing between 255-261 g) were grouped into five (A, B, C, D and E), with their parasitaemia levels and packed cell volumes (PCV) all determined before the analysis. Each rat was then injected with blood sample infected with the Trypanosoma brucei parasite. The infected rats were allowed to stay untreated for six days, during which the parasitaemia level for each of the rats was determined at two days intervals. The crude extract of the leaves of Moringa aleifera (200 mg/Kg) was orally administered ad libitum six days post-infection to rats in the first four groups (A, B, C and D), while the last group (E) was orally given distilled water (free from the extract). The effect of the extract on trypanosome-infected and treated rats was monitored for 6 days (at 2 days intervals). This was done by determining the changes in the parasitaemia levels and the packed cell volumes (PCV) of the blood of the rats. The results showed a significant decrease in the parasitaemia levels after treatment with the extract, with significant gain in the PCV of the treated rats. However, results from the untreated group (E) was not encouraging, as three of the untreated rats died before the end of the study.